'Epinephrine-resistant' angioedema. (28th January 2016) - Ange, Nikhita; Rabbolini, David J; Pidcock, Michael; Randall, Katrina L
Abstract : A man in his 60s was brought to the emergency department, with airway compromise and dysarthria due to a grossly enlarged tongue. As he was on a current course of antibiotics, he was treated for a likely antibiotic-associated allergic reaction. However, as he failed to improve with intramuscular and nebulised epinephrine, another cause of his symptoms was sought. Further discussion revealed a history of chronic lymphocytic leukaemia (CLL), which had recently relapsed. Investigations were ordered to confirm that the symptoms were due to acquired angioedema, and the patient was managed for this diagnosis based on the presence of an undetectable C4 level. This diagnosis was later confirmed when the results of specialist tests became available. The patient was treated for his relapsed CLL with good effect, and has had no further episodes of angioedema and an improvement in the level of his C1 esterase protein level and function.